Dôre Michelut: Voicing One’s Linguistic and Existential Hybridity Through Multilingual Writing and Self Translating - Spagnuolo, Elena (Italian Canadiana, 2023)
This article investigates the practice of self-translation in the context of migration by examining the literary production of Dôre Michelut, a Canadian author of Italian origins. It specifically illustrates how Michelut’s writing and translating are rooted in her migrant experience and operate as instruments through which the author can voice her hybrid identity and bridge Italian and Canadian worlds. Michelut’s experience of living in-between multiple linguistic and cultural spaces is recreated on the written page, which becomes the site where these multiple spaces are connected and interwoven. The act of writing and translating are thus interrelated in a continuous process of creation that leads to the production of a “hybrid text” and to the enactment of a “hybrid process.” In the first case, hybridity emerges through multilingual writing. In the second case, it is articulated around a specific form of self-translation that is in-between writing and translating.